Synapsis Expression Increased By Mozart’s Music Stimulation Compared With Indonesian Pop And Religious Music - Ukhti Mukminah ilmi Amila; Hermanto Tri Joewono; Widjiati Widjiati (Universitas Muhammadiyah Malang, 2020)
Classical music stimulation is a proven method that affect intelligence as well as brain function. Mozart’s classical music is classical music that could stimulate the growth of synaptic networks. To analyze the difference of synapsin expression of the brain of Rattus norvegicus offspring on Mozart’s, pop, religious and without music stimulation during pregnancy. Experimental. Treatments were subjected to Rattus norvegicusas a subject organism, initiated on the 10th day of pregnancy, in 1 hour duration in a soundproof chamber, intensity of 65 dB. On the 19th day of pregnancy the subjects were sacrificed and three offsprings were chosen. The head of the chosen Rattus norvegicusoffsprings were decapitated and the brain subsequently sectioned to calculate synapsin expression by immunohistochemistry method with 400 magnification strength microscope on the 5 field of view. Significant difference of synapsin expression of the brain of Rattus norvegicus offspring was observed between Mozart’s and control group. Significant differences of synapsin expressions were observed in the cerebellum of the newly born Rattus novergicus between Mozart and pop music groups (p = 0,007), Mozart and religious music groups (p = 0,008), Mozart and without music groups (p = 0,004).Synapsin expression of Rattus norvegicus brain offsprings were higher in Mozart music stimulation compared with pop and religious music stimulation